2019
DOI: 10.1111/eva.12802
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the efficacy of genetic shifting in control of mosquito‐borne diseases

Abstract: Many of the world's most prevalent diseases are transmitted by animal vectors such as dengue transmitted by mosquitoes. To reduce these vector‐borne diseases, a promising approach is “genetic shifting”: selective breeding of the vectors to be more resistant to pathogens and releasing them to the target populations to reduce their ability to transmit pathogens, that is, lower their vector competence. The efficacy of genetic shifting will depend on possible counterforces such as natural selection against low vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Because no new genetic material is introduced, just increasing frequencies of already existing refractory alleles, this method has been called “genetic shifting”. Recent modeling has indicated that size and number of releases needed to significantly lower the ability of the target population to transmit are realistically achievable [77]. Because the release strain is identical to genotypes already present, mating discrimination is less likely to evolve and if it does, new strains for release could be re-selected from the target population.…”
Section: Importance Of Vector Variation In Control Programsmentioning
confidence: 99%
“…Because no new genetic material is introduced, just increasing frequencies of already existing refractory alleles, this method has been called “genetic shifting”. Recent modeling has indicated that size and number of releases needed to significantly lower the ability of the target population to transmit are realistically achievable [77]. Because the release strain is identical to genotypes already present, mating discrimination is less likely to evolve and if it does, new strains for release could be re-selected from the target population.…”
Section: Importance Of Vector Variation In Control Programsmentioning
confidence: 99%
“…We assume the released mosquitoes are 5 days old when starting the simulation (i.e., time spent in the laboratory/facility before being released), and that they have a lower VC ( Table 2 ). 7 Blood-fed mosquito females enter the simulation at the beginning of the oviposition phase, in contrast to the non-fed and wild mosquitoes which begin in the biting phase ( Figure 1B ). Although we recognize that Ae.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Robert et al 6 showed that bi-sex or female-only releases have higher efficiency at reducing mosquito population density. Recently, Xia et al 7 modeled a proposed scheme, first made by Powell and Tabachnick, 8 and named “genetic shifting,” to genetically modify natural mosquito populations by releasing mosquitoes selected in the laboratory to be refractory to transmission using classical artificial selection methods. The capacity of transmitting diseases in mosquitoes is at least partially genetically determined, 9 , 10 so releasing refractory mosquitoes could alter the gene pools in the target mosquitoes and “shift” the subsequent generations to be less competent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations